Thursday

October 27, 2016
Posted by **Anna-Marie** on Monday, January 28, 2008 at 7:24pm.

5x^2 - 11x - 36 = 0

theres some kind of box trick or somethin to factor that but i forget!

- math -
**Damon**, Monday, January 28, 2008 at 7:29pmThree possible tricks

1. quadratic equation

2. complete the square

3. factor it - math -
**Damon**, Monday, January 28, 2008 at 7:33pmfactoring

(5x+9)(x-4) = 0

x = -9/5

or

x = 4 - math -
**mk-tintin**, Monday, January 28, 2008 at 7:33pmi'm french so i don't know how do u solve this equation in usa

5x^2 - 11x - 36 = 0

11²-4*5*(-36)=121+720=841

sqrt(841)=29

solutions are (11-29)/(2*5) and (11+29)/(2*5) - math -
**Anna-Marie**, Monday, January 28, 2008 at 7:35pmumm... i don't remember how to do any of it. like to factor and get the ( ) ( ) can you tell me how to do that

- math -
**Anna-Marie**, Monday, January 28, 2008 at 7:36pmooh.. damon how did you get the (5x+9)(x-4) = 0 that's what i need to know

- math -
**Damon**, Monday, January 28, 2008 at 7:39pmcomplete the square

5 x^2 - 11 x = 36

x^2 - 11/5 x = 36/5

x^2 -11/5 x + 121/100 = 36/5 + 121/100

(x-11/10)^2 = 841/100

x-11/10 = +/- 29/10

x = (11+29)/10 = 4

or

x = (11-29)/10 = -18/10 = -9/5 - math -
**Damon**, Monday, January 28, 2008 at 7:43pmOh, ok, I guessed'

Like so

5 is only 5 * 1

so there has to be something like

(5x + ;;;) (x - :::)

now the Plus and minus may change and 36 has factors

2*2*3*3

which could be 12 and 3

or 6 and six

or 9 and 4

turns out 9 and 4 work - math -
**Damon**, Monday, January 28, 2008 at 7:46pmTin tin is using some form of quadratic equation

x = -b/2 +/- (1/2) sqrt{ b^2 - 4 a c}

if in form

a x^2 + b X + c = 0- Forgot a in denominator -
**Damon**, Monday, January 28, 2008 at 7:47pmx = -b/2a +/- (1/2a) sqrt{ b^2 - 4 a c}

if in form

a x^2 + b X + c = 0

- Forgot a in denominator -
- math -
**Damon**, Monday, January 28, 2008 at 8:09pmBy the way, the quadratic equation really is completing the square

a x^2 + b x + c = 0

x^2 + (b/a) x = -(c/a)

x^2 + (b/a) x + (b/2a)^2 = -(c/a) +(b/2a)^2

(x + b/2a)^2 = [-c/a + (b/2a)^2 ]

so

x+ b/2a = +/- sqrt (b^2/4a^2 - 4 a c/4a^2)

or

x = -b/2a +/- (1/2a)sqrt(b^2-4 a c)